Where radio dare not tread: Podcasts as queer audio media. - Drushel, Bruce (Radio Journal: International Studies in Broadcast & Audio Media, 2023)
Even given its focus on narrowly defined audiences, contemporary radio in the United States is commercial, and thus dependent upon a consumer goods sector that is market-driven, risk-averse and fearful of recrimination by those opposed to homosexuality or non-binary genders and government regulators. Queer listeners, unlike their straight counterparts, found in radio not mentors to guide them through adolescence and into adulthood, but the ultimately doomed task of attempting to conform to standards and rituals that did not fit them or to alternative readings of the texts found in radio's music lyrics, disc jockey patter and commercials that constructed a world that were a better fit. In this article, I examine a varied and representative collection of podcasts and argue that the medium is uniquely positioned to deliver to queer audiences what conventional commercial radio was unwilling or unable to.